Variable Sampling Composite Observer Based Frequency Locked Loop and its Application in Grid Connected System - ARUN, K.; SELVAJYOTHI, K. (Advances in Electrical and Computer Engineering)
A modified digital signal processing procedure is described for the on-line estimation of DC, fundamental and harmonics of periodic signal. A frequency locked loop (FLL) incorporated within the parallel structure of observers is proposed to accommodate a wide range of frequency drift. The error in frequency generated under drifting frequencies has been used for changing the sampling frequency of the composite observer, so that the number of samples per cycle of the periodic waveform remains constant. A standard coupled oscillator with automatic gain control is used as numerically controlled oscillator (NCO) to generate the enabling pulses for the digital observer. The NCO gives an integer multiple of the fundamental frequency making it suitable for power quality applications. Another observer with DC and second harmonic blocks in the feedback path act as filter and reduces the double frequency content. A systematic study of the FLL is done and a method has been proposed to design the controller. The performance of FLL is validated through simulation and experimental studies. To illustrate applications of the new FLL, estimation of individual harmonics from nonlinear load and the design of a variable sampling resonant controller, for a single phase grid-connected inverter have been presented.